Analisis Dimensi Mutu Pelayanan Terhadap Kepuasan Pasien di Tempat Pendaftaran Pasien Rawat Jalan Puskesmas Batu Kota Batu - Askarila, Amira Aldini; Kholidah, Diniyah (Politeknik Kesehatan Kemenkes Malang, 2024)
Quality health services not only meet procedural standards, but must also be able to provide a satisfactory experience for patients. This study aims to analyze the influence of five service quality dimensions—tangible, reliability, responsiveness, assurance, and empathy—on patient satisfaction at the outpatient registration desk of Puskesmas Batu. The research employed a descriptive-correlational method with a cross-sectional approach. The sample consisted of 100 respondents selected through quota sampling. Data were collected using a Likert-scale questionnaire and analyzed using the Chi-Square test. The findings revealed that all service quality dimensions had a significant relationship with patient satisfaction (p-value < 0.05). The reliability and assurance dimensions showed the highest agreement level at 95%, followed by tangible (93%), empathy (91%), and responsiveness (81%). Responsiveness had the highest disagreement rate at 19%, indicating the need for special attention to staff responsiveness in meeting patient needs. The study highlights that consistent, reliable, and secure service quality is crucial in building patient satisfaction. However, shortcomings in responsiveness remain a challenge that requires immediate action.